GENDER AND AGE SPECIFIED PREVALENCE OF OSTEOPOROSIS ANDOSTEOPENIA IN AN APPARENTLY HEALTHY PAKISTANI POPULATION - Zuneera Akram; Fatima Zahra; Rehana Perveen; Muzammil Hussain; Aisha Noreen; Maryam Inayat; Sobia Akhter; Usman Ghani Farooqi (Baqai Journal of Health Sciences)
Objective: It is a crucial to understand the pattern of Bone Mineral Density (BMD) in a population to prevent and manage the complication of osteoporosis along with diagnosis. The purpose of the study is to evaluate the factors causing osteoporosis in an apparently healthy population and examine the bone health status. Methodology: A retrospective study was performed by examining the medical records in a Muneefa cardiac and general clinic for those subjects who had done with BMD measurements for preventive health checksup. The BMD was measured by using a Sonost 3000(Ultrasound Bone Densiometer) from Osteosys CO. Ltd. Korea. Results: About 161 subjects of aged 50.0±12.4 years (range: 20–70 years) were assessed, which included 93 male subjects which is 57.7% and 68 female subjects which is 42.23%. The evaluation of data revealed that 13.26% of the subjects fall under the category of Osteoporosis, in which 17.64% were female and 10.75% were male, while 22.98% subjects fall under the category of osteopenia in which 30.88% were female and 17.20% were male. Prevalence ratio of osteoporosis is higher in female subjects than male. According to the category of age - groups (20–29, 30–39, 40–49, 50–59, 60–69, and =70 years) in males osteoporosis rate were 30, 20, 20, 10, 10, and 10 percent respectively, while prevalence in females were 8.33, 16.66, 8.33, 25, 25, and 16.66 percent respectively, at peripheral (radius) bone. Body mass index, and lifestyle including (smoking, physical activity, and diet) were correlated with BMD. In elderly patients’ osteoporosis and osteopenia are common conditions that can seriously affect their quality of life. Conclusion: Further prospective studies are required to elucidate the comparative importance of nutritional status, level of activity, medication usage, and other factors in the pathways that correlate age and gender specified illnesses to BMD.